Navigating scientific lexicon: Revolutionizing scientific terminology instruction through mortrex framework/ Norazha Paiman - Paiman, Norazha (2023)
Navigating the realm of scientific terminology poses a formidable challenge for many ESL undergraduate students, particularly those for whom English is a second language (ESL). The Morpheme-Oriented Tree of Lexicogenic Extensions (MORTREX) framework was used to create a new theoretical framework that helps English as a Second Language (ESL) students learn and improve their scientific vocabulary. This conceptual framework aims to provide a comprehensive understanding of the organization, expansion, and functional aspects of morphemes within a language. The MORTREX framework elucidates the hierarchical arrangement of morphemes and their relationships, focusing on how they contribute to the formation and expansion of words through the addition of extensions. This framework facilitates the analysis, categorization, and exploration of morphemes, shedding light on their roles in language structure, development, and meaning. The results of implementing the MORTREX framework are represented in the form of a continuous mind map. This visual representation highlights the remarkable ability of students to generate branching extensions and new terminologies stemming from their chosen scientific term. This outcome underscores the pivotal role of a solid understanding of word formation processes in expanding students’ grasp of scientific terminology, thereby enhancing their terminology acquisition. The findings of this study emphasize the symbiotic relationship between knowledge of word formation and the broader acquisition of scientific terminology. By cultivating a deeper comprehension of morphemic constituents and their interconnections, students are empowered to significantly expand their terminology repertoire. Consequently, this study calls attention to the importance of incorporating explicit teaching of word formation processes into curricula aimed at enhancing students’ grasp of scientific language. In conclusion, this research offers valuable insights for curriculum developers and instructors of content courses. By integrating targeted instruction on word formation, educators can effectively enhance students' ability to acquire and master scientific terminology.